Minimum inhibitory concentrations of penicillin and minocycline for 300 isolates of N. gonorrhoeae. Issue 4 (August 1975) - Shahidullah, M; Greaves, P W
Abstract : The minimum inhibitory concentrations of penicillin and minocycline were measured on 300 consecutive isolates of N. gonorrhoeae from patients attending the Nottingham treatment centre. 210 (70 per cent.) of these were fully sensitive to penicillin (MIC less than 0-1 mug./ml) and 89 per cent. were fully sensitive to minocycline (MIC less than 0-5 mug./ml.). Of the nine strains resistant to penicillin (MIC less than or equal to 0-5 mug./ml.), eight were also of reduced sensitivity to minocycline.